2012
DOI: 10.1088/0022-3727/45/23/235106
|View full text |Cite
|
Sign up to set email alerts
|

A tunable hybrid metamaterial absorber based on vanadium oxide films

Abstract: A tunable hybrid metamaterial absorber (MA) in the microwave band was designed, fabricated and characterized. The hybrid MA was realized by incorporating a VO2 film into the conventional resonant MA. By thermally triggering the insulator–metal phase transition of the VO2 film, the impedance match condition was broken and a deep amplitude modulation of about 63.3% to the electromagnetic wave absorption was achieved. A moderate blue-shift of the resonance frequency was observed which is promising for practical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
61
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(62 citation statements)
references
References 26 publications
0
61
0
1
Order By: Relevance
“…This semiconductor-to-metal transition (SMT) takes place when a thermal, electrical, magnetic or optical stimulus is applied and it can occur at ultrafast timescales (~100 fs) [12][13][14]. Recently, considerable efforts have focused on fabricating frequency tunable active metamaterials exhibiting narrow-band operation for a given portion of the electromagnetic spectrum, including microwave, THz and optical frequencies, by tuning the electrical and magnetic modes of SRRs using the phase changing properties of VO 2 [15][16][17]. In this paper, we demonstrate hybrid metamaterial devices designed for multi-band THz frequencies by fabricating double SRR arrays on VO 2 films by a conventional lift off process.…”
Section: Introductionmentioning
confidence: 99%
“…This semiconductor-to-metal transition (SMT) takes place when a thermal, electrical, magnetic or optical stimulus is applied and it can occur at ultrafast timescales (~100 fs) [12][13][14]. Recently, considerable efforts have focused on fabricating frequency tunable active metamaterials exhibiting narrow-band operation for a given portion of the electromagnetic spectrum, including microwave, THz and optical frequencies, by tuning the electrical and magnetic modes of SRRs using the phase changing properties of VO 2 [15][16][17]. In this paper, we demonstrate hybrid metamaterial devices designed for multi-band THz frequencies by fabricating double SRR arrays on VO 2 films by a conventional lift off process.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these tuning approaches utilizes the change in material properties of the structural materials or surrounding medium. The various means of external control such as optical [12], electrical [13], mechanical [14], thermal [15], or magnetic [16] have been reported so far. However these tuning methods usually involve exotic materials, and so have limited response with non-linear characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 Tunable metamaterial absorbers in the microwave 24 and THz regimes 25 were designed by using VO 2 film as the ground plane to modulate the impedance match conditions for splitring resonators (SRRs). Dicken et al 26 reported a metamaterial with tunable resonance frequency in the near-infrared by depositing SRRs on a continuous VO 2 film, which modulates surface plasmon at different phases.…”
mentioning
confidence: 99%